2012
DOI: 10.1063/1.4765103
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation mechanisms of excited CH3X (X = Cl, Br, and I) formed via high-energy electron transfer using alkali metal targets

Abstract: High-energy electron transfer dissociation (HE-ETD) on collisions with alkali metal targets (Cs, K, and Na) was investigated for CH(3)X(+) (X = Cl, Br, and I) ions by a charge inversion mass spectrometry. Relative peak intensities of the negative ions formed via HE-ETD strongly depend on the precursor ions and the target alkali metals. The dependency is explained by the exothermicities of the respective dissociation processes. Peak shapes of the negative ions, especially of the X(-) ions, which comprise a tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…These trapezoidal profiles indicated that the dissociation of the 17 u loss from the precursor ions suggested a spontaneous process from a state with a specific internal energy, as found in the previous results for methanol [39], CH 2 X 2 [43], and CH 3 X ions [45]. To discuss the dissociation mechanism in conjunction with AEs, KER values are …”
Section: N C˛ Bond Cleavagementioning
confidence: 74%
See 3 more Smart Citations
“…These trapezoidal profiles indicated that the dissociation of the 17 u loss from the precursor ions suggested a spontaneous process from a state with a specific internal energy, as found in the previous results for methanol [39], CH 2 X 2 [43], and CH 3 X ions [45]. To discuss the dissociation mechanism in conjunction with AEs, KER values are …”
Section: N C˛ Bond Cleavagementioning
confidence: 74%
“…The ratio of the KER values to the averaged AE value is 62%. This large ratio implied that most of the internal energy was released as kinetic energy at the dissociation via repulsive potential, similar to that of the small organic cations [36,39,43,45]. On the other hand, C N bond cleavage from the hypervalent ammonium radical in methyl ammonium to result in the NH 3 loss was reported from the neutral detection experiment by Porter and coworkers [16] and from the NRMS method by Turecek [35].…”
Section: N C˛ Bond Cleavagementioning
confidence: 86%
See 2 more Smart Citations
“…Charge inversion mass spectrometry has also provided information concerning the dissociation pathways of energy-selected neutral species, such as CH n (n=3-5), 44) C 2 H 2 , 45) C 3 H 4 , 46) chlorophenol, 47) and methyl stearate. 48) e dissociation of energy selected neutral of halogen containing simple molecules, such as CH 2 X 2 49,50) and CH 3 X (X=Cl, Br, I) 51) showed a strong dependence on both the target species and halogen in the molecules in charge inversion spectra using alkali metal targets (Cs, K and Na). While the CHCl 2 − ion was predominant in the spectra of CH 2 Cl 2 + regardless of target species, the most intense peaks were CH 2 Br 2 + and CH 2 I 2 + were ascribed to being derived from either Br − or CH 2 Br − and either I − or I 2 − , respectively, depending on the target metal used.…”
Section: Charge Inversion Mass Spectrometrymentioning
confidence: 99%